2015
DOI: 10.1007/s11102-015-0684-z
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting biochemical control response rates with first-generation somatostatin analogues in acromegaly

Abstract: ContextThe somatostatin analogues octreotide LAR and lanreotide Autogel have been evaluated for the treatment of acromegaly in numerous clinical trials, with considerable heterogeneity in reported biochemical response rates. This review examines and attempts to account for these differences in response rates reported in the literature.Evidence acquisitionPubMed was searched for English-language studies of a minimum duration of 24 weeks that evaluated ≥10 patients with acromegaly treated with octreotide LAR or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 53 publications
3
58
3
3
Order By: Relevance
“…Clinical data supporting efficacy and safety of first-generation SSAs, long-acting octreotide [21] and lanreotide Autogel [22], in Japanese patients with acromegaly have previously been reported. In most of the studies, the response rate in patients treated with first-generation SSAs ranges from 17% to 41% [2,[23][24][25]. In a retrospective study, pegvisomant monotherapy showed efficacy with sustained IGF-1 normalization in Japanese patients with acromegaly; however, there was no effect on GH reduction and tumor shrinkage, and safety concerns like liver toxicity were observed [26], which is consistent with the known profile of pegvisomant.…”
Section: Discussionsupporting
confidence: 57%
“…Clinical data supporting efficacy and safety of first-generation SSAs, long-acting octreotide [21] and lanreotide Autogel [22], in Japanese patients with acromegaly have previously been reported. In most of the studies, the response rate in patients treated with first-generation SSAs ranges from 17% to 41% [2,[23][24][25]. In a retrospective study, pegvisomant monotherapy showed efficacy with sustained IGF-1 normalization in Japanese patients with acromegaly; however, there was no effect on GH reduction and tumor shrinkage, and safety concerns like liver toxicity were observed [26], which is consistent with the known profile of pegvisomant.…”
Section: Discussionsupporting
confidence: 57%
“…8,14 However, many patients fail to achieve biochemical control with somatostatin analogues. 15 Pegvisomant is useful in patients who are inadequately controlled by somatostatin analogues, A Β Figure 4. Pasireotide suppressed GH (A) and IGF-1 (B) in patient 2 resistant to multiple treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical control rates of approximately 55% have been reported with the first-generation SRLs octreotide and lanretotide 60 ; however, data from rigorously conducted trials using currently available long-acting formulations show lower rates of 25-45% 16,17,19,61 (MQ). As patient selection bias, initial IGF1 levels, previous surgery, adverse effects and treatment compliance can all impact the likelihood of achieving biochemical control, in practice, biochemical response to first-generation SRLs is likely to be higher than that observed in trials published in the past 10 years but lower than in earlier trials (LQ) 62 . Octreotide long-acting release (LAR) is administered once monthly by intramuscular injection; lanreotide autogel is administered once monthly subcutaneously by the patient, their caregiver or a health-care provider.…”
Section: Somatostatin Receptor Ligandsmentioning
confidence: 98%